A Comparative study on Bengali handwritten character recognition and prediction using CNN - Abrar, Muntaqa; Kadir, Md Nazial; Faruk, Tabassum (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.